In vitro and in vivo virulence of Salmonella Typhimurium DT104 : a parallelogram approach - Berk, Petra Angeli, ....- (Wageningen : Wageningen University, 2008)
Salmonella is present in different food products. In this research it is concluded that Salmonella, which can survive the stomach of humans better (acid resistant bacteria), have a higher probability of causing an infection than Salmonella strains that are less able to survive the stomach (acid sensitive bacteria). The probability of such an infection is determined using different model systems. Effects on an infection with cultured human and rat intestinal cells were comparable to results obtained with a rat model. The probability of infection calculated with the results from both model systems agree with data from human experiments conducted in the fifties and with epidemiological dose response data. If these results can be founded by additional research, with different Salmonella species, it could be possible to reduce the amount of animal experiments in the future.
Proefschrift ter verkrijging van de graad van doctor
Keywords: Voedselvergiftiging